Shrimp Chemoattraction and Feeding Stimulation: Methods, Progress and Significance - Lawrence, A.L.; Walker, S.; Brister, J.; Hicks, D.; Bray, W.; Fox, J. (Avances en Nutrición Acuicola, 2019)
For many academic and commercial feed nutritionists, the identification of cost-effective chemoattractants and feeding stimulates (CFS) for shrimp has the highest priority in the area of shrimp nutrition and feed management. CSF are dependant upon chemoreception of one or more chemicals in solution. Chemorecption is defined as transduction of any type of chemical stimuli into a nervious impulse. Significant progress as been made since the major review was done my Lee and Myers in 1997. What most individuals refer to as attractability can more accurately be referred to as a behavioral response to CFS. Lee and Myers proposed five distinct phases consisting of detection, orientation, locomotion, initiation of feeding and continuation of feeding. Conceptionally, this indicates the potential of five separate receptor sites on the animal with five distinct chemical requirements. Further, one has to also assume that there are interactions or synergisms and inhibitions or suppressors in response to CFS. Because of these complexities and with the difficultly of developing a predictable and reliable method to measure one or more of the preceding phases with the necessary statistical package; it is not surprising that progress in this critical area of shrimp nutrition and feed development has been lacking.